Comparative transcriptome analysis of equine alveolar macrophages. (9th July 2016) - Karagianni, A.E.; Kapetanovic, R.; Summers, K.M.; McGorum, B.C.; Hume, D.A.; Pirie, R.S.
Summary: Reasons for performing study: Alveolar macrophages (AMs) are the first line of defence against pathogens in the lungs of all mammalian species and thus may constitute appropriate therapeutic target cells in the treatment and prevention of opportunistic airway infections. Therefore, acquiring a better understanding of equine macrophage biology is of paramount importance in addressing this issue in relation to the horse. Objectives: To compare the transcriptome of equine AMs with that of equine peritoneal macrophages (PMs) and to investigate the effect of lipopolysaccharide (LPS) on equine AM. Study design: Gene expression study of equine AMs. Methods: Cells from both bronchoalveolar and peritoneal lavage fluid were isolated from systemically healthy horses that had been submitted to euthanasia. Cells were cryopreserved. RNA was extracted and comparative microarray analyses were performed in AMs and PMs, and in AMs treated and untreated with LPS. Comparisons with published data derived from human AM studies were made, with particular focus on LPS‐induced inflammatory status. Results: The comparison between AMs and PMs revealed the differential basal expression of 451 genes. Gene expression analysis revealed an alternative (M2) macrophage polarisation profile in AMs and a hybrid macrophage activation profile in PMs, a phenomenon potentially attributable to a degree of induced endotoxin tolerance. The gene expression profile of equine AMs following LPS stimulation revealed significant changes in the expression of 240 genes, including well‐known upregulated inflammatory genes. This LPS‐induced gene expression profile of equine AMs more closely resembles that of human rather than murine macrophages. Conclusions: This study improves current understanding of equine macrophage biology. These data suggest that the horse may represent a suitable animal model for the study of human macrophage‐associated lung inflammation and data derived from human macrophage studies may have significant relevance to the horse.